Cephalometric characteristics of autochthonous population in the Republic of Kazakhstan - M. M. Soloviev; C. E. Ormanov; L. A. Aleksina; A. A. Baindurashvili (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
Front and side view photos of 320 Kazakh and Uzbek residents of Kazakhstan were studied by means of photo grammetry and a computer aided program «Harmony». Analysis of 46 cephalometric parameters resulted in the following findings: statistically significant difference between Uzbek and Kazakh males was detected in 39,1 % of the cases, while those among females were noted in 54,3 %, of the cases, i. e. ethnic distinctions were more pronounced in the females. An architectonic comparison of Kazakh and Uzbek facial features with the European types of faces has revealed that the facial features of the Kazakh females bear a stronger similarity to the Caucasoid facial types.